Strengthening Environmental Awareness through Community-Based Cleanup Initiatives in Gampong Lambheu - Fitriyani Fitriyani; Asri Diana; Siti Laiya Maharani; Zalfa Ronna; Miftahul Jannah; Faiz Muhammad Bariq Lubis; Fakhruddin Fakhruddin; Cut Zakia Rizki (Jurnal Pengabdian Bakti Akademisi, 2026)
This community service activity aims to increase awareness and involvement of residents, especially students, in maintaining the cleanliness of the village environment. This mutual cooperation activity was carried out at the Geuchik's Office and Meunasah Gampong Lambheu, involving students, village officials, and local residents. This activity includes cleaning the area around the office and meunasah, counseling on the importance of cleanliness, and reorganizing cleaning facilities in the area. The results of this activity showed an increase in residents' awareness of the cleanliness of public facilities and created a cleaner and more organized environment.